Who Should Be at the Top of Bottom-Up Development? A Case-Study of the National Rural Livelihoods Mission in Rajasthan, India - Joshi, Shareen; Rao, Vijayendra (Taylor and Francis, 2018)
It is widely acknowledged that top-down support is essential for bottom-up participatory projects to be effectively implemented at scale. However, which level of government, national or sub-national, should be given the responsibility to implement such projects is an open question, with wide variations in practice. This paper analyses qualitative and quantitative data from a natural experiment of a large participatory project in the state of Rajasthan in India comparing central management and state-level management. We find that locally managed facilitators formed groups that were more likely to engage in collective action and be politically active, with higher savings and greater access to subsidized loans.